Eksplorasi Perbandingan Manajemen Kurikulum Konvensional Dengan Kurikulum Merdeka - Muhammad Husaini (https://journal.metanusantara.com/jenius/index.php/jem, 2024)
Education in Indonesia is undergoing a significant transformation with the introduction of Merdeka Curriculum which aims to increase flexibility and innovation in teaching. This study aims to compare conventional curriculum management with Merdeka Curriculum in the context of schools in Cepu, Central Java. This research uses a qualitative approach with the main data sources being in-depth interviews and observations. The research informants included teachers, principals, and students from schools that implemented both curricula. The purpose of this study was to explore the experiences, perceptions, and practices of stakeholders related to the implementation of the two curricula. The results showed that teachers in schools implementing Merdeka Curriculum reported increased flexibility in teaching and evaluation methods, as well as higher student motivation. In contrast, teachers in schools with the conventional curriculum felt limited by the rigid curriculum structure and complicated bureaucracy. Students in schools with Merdeka Curriculum also feel more motivated and involved in the learning process.